Adaptable Hydrogels Mediate Cofactor‐Assisted Activation of Biomarker‐Responsive Drug Delivery via Positive Feedback for Enhanced Tissue Regeneration. Issue 12 (22nd October 2018) - Zhang, Kunyu; Jia, Zhaofeng; Yang, Boguang; Feng, Qian; Xu, Xiao; Yuan, Weihao; Li, Xingfu; Chen, Xiaoyu; Duan, Li; Wang, Daping; Bian, Liming
Abstract: The targeted and simultaneous delivery of diverse cargoes with vastly different properties by the same vehicle is highly appealing but challenging. Here, a bioactive nanocomposite hydrogel based on hyaluronic acid and self‐assembled pamidronate‐magnesium nanoparticles for the localized elution and on‐demand simultaneous release of bioactive ions and small molecule drugs is described. The obtained nanocomposite hydrogels exhibit excellent injectability and efficient stress relaxation, thereby allowing easy injection and consequent adaptation of hydrogels to bone defects with irregular shapes. Magnesium ions released from the hydrogels promote osteogenic differentiation of the encapsulated human mesenchymal stem cells (hMSCs) and activation of alkaline phosphatase (ALP). The activated ALP subsequently catalyzes the dephosphorylation (activation) of Dex phosphate, a pro‐drug of Dex, and expedites the release of Dex from hydrogels to further promote hMSC osteogenesis. This positive feedback circuit governing the activation and release of Dex significantly enhances bone regeneration at the hydrogel implantation sites. The findings suggest that these injectable nanocomposite hydrogels mediate optimized release of diverse therapeutic cargoes and effectively promote in situ bone regeneration via minimally invasive procedures. Abstract : A bioactive nanocomposite hydrogel is fabricated to mediate the localized delivery and regeneration‐specific release of bioactive ions and small molecule drugs. This nanocomposite hydrogel exhibits excellent injectability and efficient stress relaxation, thereby allowing easy injection into bone defects with irregular shapes. The positive feedback circuit of drug release regulation from hydrogels can significantly promote in situ bone regeneration.